Geotourism management for sustainable development of tourism: A bibliometric analysis of the main research areas and domains of knowledge - Rocío Hernández-Garrido; Jaime Orts-Cardador; Cinta Perez-Calañas (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2023)
Geotourism has attracted an increasing academic interest in recent years due to the new demands of society for sustainable and alternative destinations and its their effective management is essential. This study conducts a comprehensive bibliometric analysis of geotourism management covering research published from 1991 to June 2023. The objective of this study is to perform a bibliometric analysis to demonstrate the current research and key findings on geotourism management. In addition, we identify the existing limitations in the current literature to show research trends and future directions. To achieve this objective, we analysed 813 publications with 10,937 cited references from Web of Science. Our analysis encompassed three key bibliometric techniques (co-authorship, co-citation and co-occurrence of keywords). The main results show the increasing popularity and investigations in geotourism and destination management. Using mapping techniques, our study shows the relevance of research in geoconservation, sustainable tourism and, to a lesser extent, in geological heritage. The findings contribute to a broad and diverse understanding of the management of geotourism, which can provide insights for DMOs and policymakers in establishing proper management in geotourism to ensure conservation in geodestinations.